Recycling Organic Materials to Improve Your Florida-Friendly Edible Landscape - Terra Freeman; Tiare Silvasy; Lynn Barber; Tom Wichman; Esen Momol; Kristina McIntyre; Jacqlyn Rivas; Jen Marvin (EDIS)
This new 7-page publication of the UF/IFAS Environmental Horticulture Department is intended to educate homeowners on environmentally friendly ways to enhance soil fertility for vegetables, herbs, and fruits in the home landscape. It discusses strategies for recycling nutrients in place or via composting systems to create productive edible landscapes with less waste. Adopting these methods into your landscape maintenance routine will build organic matter and add nutrients to the soil naturally. Written by Terra Freeman, Tiare Silvasy, Lynn Barber, Tom Wichman, Esen Momol, Tina McIntyre, Jacqlyn Rivas, and Jen Marvin. https://edis.ifas.ufl.edu/ep599